2023
DOI: 10.3390/insects14050465
|View full text |Cite
|
Sign up to set email alerts
|

Research on Photoinduction-Based Technology for Trapping Asian Longhorned Beetle (Anoplophora glabripennis (Motschulsky, 1853) (Coleoptera: Cerambycidae)

Abstract: Light traps play a crucial role in monitoring pest populations. However, the phototactic behavior of adult Asian longhorned beetle (ALB) remains enigmatic. To provide a theoretical foundation to select the suitable light emitting diode (LED)-based light sources used for monitoring ALB, we compared the effect of exposure time on the phototactic response rates of adults at wavelengths of 365 nm, 420 nm, 435 nm, and 515 nm, and found that the phototactic rate increased gradually when the exposure time was prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that Coleoptera beetles display a preference for UV, violet and green wavelength spectra (350-440 and 500-560 nm) (Kim et al, 2019;Van der Kooi et al, 2021). Using the same behavioral response chamber, both females and males A. glabripennis displayed higher phototactic responses under illumination with 420 and 435 nm wavelengths (violet and blue) at night, with an approximately 74%-82% trapping rate (Jiang et al, 2023a). UV light traps were more attractive to Arhopalus ferus and Prionoplus reticularis (longhorn beetles) than their adjacent two yellow lights .…”
Section: Figurementioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies have shown that Coleoptera beetles display a preference for UV, violet and green wavelength spectra (350-440 and 500-560 nm) (Kim et al, 2019;Van der Kooi et al, 2021). Using the same behavioral response chamber, both females and males A. glabripennis displayed higher phototactic responses under illumination with 420 and 435 nm wavelengths (violet and blue) at night, with an approximately 74%-82% trapping rate (Jiang et al, 2023a). UV light traps were more attractive to Arhopalus ferus and Prionoplus reticularis (longhorn beetles) than their adjacent two yellow lights .…”
Section: Figurementioning
confidence: 89%
“…To observe the phototactic behavior of D. helophoroides in the different conditions, a light-dark alternative apparatus with an opaque black acrylic board was self-designed based on a previous study (Figures 1A, B) (Jiang et al, 2023a). The apparatus comprised two test chambers (L = 50 cm × H = 30 cm × W = 30 cm) at right angles to each other, which provided an activity space for beetles to respond to different wavelength LED lights, and an activity chamber (L = 30 cm × H = 30 cm × W = 30 cm), which provided adequate space for insect movement.…”
Section: Experimental Apparatus and Light Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The phototaxis monitoring system ( Figure 1 ) was designed based on Huang et al (2023) and Jiang et al (2023) [ 37 , 38 ]. It included a phototactic reaction chamber (light zone), a static chamber, and a dark chamber (dark zone).…”
Section: Methodsmentioning
confidence: 99%